2019
DOI: 10.1111/ejss.12902
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal community assembly processes under long‐term fertilization

Abstract: Understanding the processes that regulate communities of microorganisms is a key issue and focus in microbial ecology. Although fungi play a critical role in soil biogeochemical cycling, their community assembly processes remain largely unknown, especially in agricultural soils. In this study, we investigated the relative importance of five community assembly processes (variable selection, homogeneous selection, homogeneous dispersal, dispersal limitation and an undominated process) in soil fungal communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Additionally, the hyphal networks of fungi and the roots of their hosts limit the dispersion of fungal species (i.e., dispersal limitation), since most of the dominant trees in the forest are EcM or arbuscular mycorrhizae ( Lu et al, 2018 ; Gurmesa et al, 2019 ). Our results support the view that stochastic processes predominate in the fungal community assembly ( Shi et al, 2019 ; Zhao J. et al, 2019 ; Jiao and Lu, 2020 ). Furthermore, the neutral community model explained a relatively large fraction ( R 2 > 0.5) of fungal community variation, indicating that the fungal community was more influenced by neutral (or stochastic) processes.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the hyphal networks of fungi and the roots of their hosts limit the dispersion of fungal species (i.e., dispersal limitation), since most of the dominant trees in the forest are EcM or arbuscular mycorrhizae ( Lu et al, 2018 ; Gurmesa et al, 2019 ). Our results support the view that stochastic processes predominate in the fungal community assembly ( Shi et al, 2019 ; Zhao J. et al, 2019 ; Jiao and Lu, 2020 ). Furthermore, the neutral community model explained a relatively large fraction ( R 2 > 0.5) of fungal community variation, indicating that the fungal community was more influenced by neutral (or stochastic) processes.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the hyphal networks, forming between fungi and the roots of their hosts, limit the dispersion of fungal species (i.e., dispersal limitation), since most of the dominant trees in the forest are ectomycorrhizal or arbuscular mycorrhizae [39,63]. In general, our results are supported by prior studies reporting that stochastic processes predominate in fungal community assembly [13,18,21]. Furthermore, the neutral community model explained a relatively large fraction (R 2 > 0.5) of fungal community variation, indicating that the fungal community was more influenced by neutral (or stochastic) processes.…”
Section: Soil Fungal Community Assembly Was Mainly Shaped By Stochastsupporting
confidence: 85%
“…Nitrogen enrichment can also affect the processes underpinning fungal community assembly but inconsistent results have been reported. For example, stochastic processes dominate under the fertilization treatment in some studies [20,21], whereas deterministic processes were found to have a larger relative importance with fertilization in other studies [31,33]. Moreover, nitrogen fertilization resulted in tightened network associations among fungal, bacterial and protists communities in diverse agricultural soils [34], indicating increased importance of deterministic biotic interactions in shaping microbiome.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have proposed an increasing proportion of deterministic processes along the chronosequence of long-term disturbances, though emphasis has been given to the stochastic processes at the initial stage of disturbance [10,11]. Although soil microbiota is jointly shaped by the deterministic and stochastic processes under anthropogenic disturbances, such as fertilization [12], climate warming [11], and land use changes [10], the relative importance of these two processes is still unclear.…”
Section: Introductionmentioning
confidence: 99%